Análisis dinámico estructural de viga cajón, de puente grúa Birráil clase d para mejorar sus condiciones de operación - Cabanillas Lezama, Rayder Fránklin (2016)
In the present thesis, a dynamic structural analysis of a D-type buckle-type crane with load capacities 5, 10, 15, 20, 25 and 30 tons and 10, 15, 20, 25 and 30 meter lights, With the aim of improving operating conditions. A survey was conducted to collect input data, which are the conditions where the main beam will operate. Four stages of analysis were performed: the former being the shape design; The second the main loads and influencing factors; The third the efforts, safety factors and deformations; And the fourth stage for dynamic beam response. Through the dynamic structural analysis and use of stiffeners in drawer beam for different lights and load states; It was possible to improve indicators such as: rigidity and weight of the birráil crane bridge. The analytical rigidity index is 30 for a beam of 10 meters’ light with a load of 30 Ton and decreasing to a value of 5.6 for the 10 meter beam, but with a load of 05 Tn. The minimum specific weight is 0.113 for a beam of 30 Ton for a light of 10 meters and increases to a value of 0.117 by adding the transverse and longitudinal stiffeners, thus reaching a value of 1.227 for the case of the beam of 30 meters of light under the load of 05 Ton with transverse and longitudinal stiffeners. The stresses and deformations for both the 10, 15, 20, 25 and 30 meter lights were calculated analytically and by simulation with lifting loads of 05, 10, 15, 20, 25, 30 tons. Being the minimum value of the effort of 66.24 for a light of 10 m and under the load of 05 Ton and its deflection of 8.90 mm.